Model Rancang Bangun Shopping Mall Di Kota Singaraja: Bahasa Indonesia - Kevin Ken; I Wayan Parwata; Ni Luh Anik Puspa Ningsih; Made Anggita Wahyudi Linggasani (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2024)
The city of Singaraja in Bali is experiencing rapid growth, primarily due to the emergence of contemporary shopping centers. Singaraja has the fastest population growth, according to census data from Bali. Contemporary shopping centers, also known as malls, are intended to offer convenience and new experiences for everyone, including children and adults. In terms of tourism, the goal is to balance modernization with the preservation of Balinese arts and culture. The modern shopping center in Singaraja aims not only to be a modern and sophisticated shopping destination but also to preserve Balinese cultural values. The methods used during the preparation of this article included surveys, field observations, documentation, and interviews. Additionally, there are several functions resulting from the design of this mall, namely: Primary Functions (focused on activities that enhance trade, goods, and services, attracting tourists to visit, such as retail outlets, exhibition areas), Supporting Functions (support facilities such as recreational areas, usually including cinemas, playgrounds, dining areas), and Service Functions (providing services such as generators, CCTV, security, toilets, visitor parking, goods loading parking). It is complemented by the concept of city walk and regionalism architecture theme to be implemented in the design of this Shopping Mall.